DYAD CHARACTERISTICS PREDICTING THE CAREGIVING EXPERIENCE:. (11th November 2018) - Williams, K; Perkhounkova, E; Shaw, C; Blyler, D; Hein, M; Seabold, D; Kim, S
Abstract: BACKGROUND Currently, 15.2 million caregivers provide care for a person with dementia (PWD) and these caregivers frequently experience stress, strain, and burden that contribute to depression, insomnia, and other negative outcomes. FamTechCare is a telehealth intervention that uses in-home video recording to link family caregivers to experts for individualized guidance in managing care. In this analysis, we examined demographic factors in relation to associated differences in self-reported baseline measures of caregiver outcomes. METHODS Multivariable models were used to evaluate relationships between demographic characteristics of the dyads and caregiver-reported measures at enrollment for 83 caregivers and 61 PWDs. Baseline measures included reliable and valid scales evaluating caregiver depression, desire to institutionalize the PWD, and frequency of and bother related to behavioral symptoms of dementia, and caregiver burden. RESULTS Compared to other relationship groups, caregiving spouses reported increased disruption (p=.03 child/spouse of child and .06 other caregivers), bother from dementia due to memory issues (p=.01 and .003) and overall behavioral symptoms (p=.05 and .01). Spouses also reported highest burden levels (p=.04 and .004). Caregivers of unmarried, widowed, or divorced PWDs reported higher levels of burden than caregivers of married PWDs (p=.01). Higher depression scores were related to longer length of caregiving (p<.001). Caregivers with higher levels of education had higher desire to institutionalize the PWD (p=.01). DISCUSSION Understanding how caregiver experiences vary based on caregiver and PWD demographic characteristics can inform the health care professionals of the need to assess caregiver perceptions of their experience and to provide targeted supportive interventions.